Login di Close The Door : Dakwah Digital Habib Ja'far Pada Generasi Z - Husna, Nihayatul (IAINU Kebumen, 2023)
The rapid progress of information and communication technology, especially in mass media or social networks, requires people to be aware of the importance of learning to use media. Generation Z is no exception, who from an early age are familiar with technology and are familiar with gadgets. Individuals within the scope of generation Z tend to utilize the mass media as a means of transferring information or even knowledge. Of course there are positive effects in the use of this mass media. One of them is as a means of broadcasting Islamic da'wah on social media. Broadcasting Islamic da'wah through various social media platforms, such as Instagram, YouTube, Tik-Tok, Podcasts, Twitter and Facebook. Not long ago, during the month of Ramadan in 1444 H Deddy Corbuzier held a special event